Composition Analysis of Salsola grandisand Its Effects on Colon Cancer Cells - Ŧ#158;irin, Seda; Dursun, Hatice Gül; GüneŦ#159, Canan EroĦ#159;lu (Anti-Cancer Agents in Medicinal Chemistry, 2023)
Background: The success of drug treatment of colon cancer (CC), which is in the top three in terms of incidence and mortality among all cancers, is adversely affected by reasons, such as severe side effects and chemoresistance. Clinical, epidemiological and experimental studies have indicated the need for developing new alternative drugs for the treatment of CC. Plants are an important source of traditional medicines that have proven to be highly beneficial for the treatment of CC. Aim: In this study, we aimed to reveal the antioxidant properties and anti-carcinogenic activity of Salsola grandis methanol extract (SGME) on HT-29. Methods: For this purpose, we used spectrophotometric methods to determine the antioxidant properties of SGME and LC-MS/MS analysis to measure the phenolic acid composition. We applied 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide, the thiazolyl blue (MTT) method, to evaluate its effects on cell viability and ELISA assay, realtime PCR, and western blot method to reveal its effects on apoptosis. Results: Spectrophotometric analyzes showed that SGME has the highest phenolic acid content, inhibits plasma lipid peroxidation and shows chelating activity and radical scavenging activity. Gene and protein expression analysis revealed the effects of SGME treatment on apoptosis genes/proteins. Conclusion: These findings showed that SGME has anticarcinogenic activity on CC due to its antioxidant, cell viability- suppressing and apoptosis-inducing properties.
Keywords: chemoprevention